Nipah Crafts and Its Impact on Communities and The Environment In 3-4 Ulu Seberang Ulu 1 District, Palembang City - Dinda Afrilla; Farida R Wargadalem (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2023)
This research is based on the lack of narrative about handicrafts from nipa leaves as one of the local wisdoms in the city of Palembang. The problem of this research is how the impact of nipah crafts on the people of 3-4 Ulu Palembang. The aim of the research is to provide knowledge of nipa palm handicrafts and their impact on the people of 3-4 Ulu Palembang city. The research uses historical methods with heuristic, criticism, interpretation, and historiography stages. The results of the study showed that the people of 3-4 Ulu Palembang city used nipah leaves for handicrafts. This utilization has an impact on the socio-economic life of the community. Nipa leaves can be made into handicrafts for dinner plates, baskets, winnowing and cigarettes. However, the nipa leaf craft has a negative impact in the form of nipa waste (klisak) which damages the environment because the nipa palm craftsmen throw the klesak on the roads passed by residents which were previously inundated with water, so they have to use bridges. After the two roads were full, some of the craftsmen dumped them in the Musi River, causing flooding. Another negative impact is sulfur fumes from the process of making nipa leaf cigarettes which causes shortness of breath.